Maternal pregnancy profile in adolescence: preliminary data for the year 2021 in the state of Paraná (Research, Society and Development, 2021)
This article presents an ecological study of the maternal profile and monitoring of teenage pregnancy, through preliminary data from the year 2021 in Paraná State and the role of the nursing professional in this situation. The research aims to evaluate the social, economic and family parameters in the pregnancy of adolescents up to 19 years of age, verifying the possible relationship with prematurity, low birth weight and other maternal-fetal health parameters. Of the pregnancies that occurred in Paraná until the month of August 2021, 11.23% occurred in single adolescents aged 10 to 19 years old, with a predominance between 15 and 19 years old. This fact becomes importante or public health and society, as a pregnancy at this age increases school dropout, greater chances of maternal-fetal complications, and can cause family conflicts. In this sense, the nurse has the role of prevention and direct guidance to adolescents in a manner appropriate to their age and ability to understand, welcoming the pregnant adolescent, and promoting the health of the mother and newborn after birth.